2020
DOI: 10.1007/s10162-020-00766-z
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Tonic Muscle Activation on Amplitude-Modulated Cervical Vestibular Evoked Myogenic Potentials (AMcVEMPs) in Young Females: Preliminary Findings

Abstract: Cervical vestibular evoked myogenic potentials (cVEMPs) are usually elicited by transient tonebursts, but when elicited by amplitude-modulated (AM) tones, they can provide new information about cVEMPs. Previous reports of cVEMPs elicited by AM tones, or AMcVEMPs, have not systematically examined the effects of tonic EMG activation on their response properties. Fourteen young, healthy female adults (ages 20-24) with clinically normal audiograms participated in this study. AMcVEMPs were elicited with bone-conduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

3
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(21 citation statements)
references
References 74 publications
3
18
0
Order By: Relevance
“…3 However, a consistent finding in transient cVEMP IAA literature is a relatively high upper limit of normal for a diagnostic criterion (e.g., upward of 40–45% asymmetry). Clinard et al 4 reported AMcVEMP IAAs for amplitude measures that were similar to IAAs of transient cVEMPs, with upper limits of normal at ∼45%; AMcVEMP interaural asymmetries for SNR and phase coherence had upper limits of ∼15%. This smaller variability in AMcVEMP interaural asymmetries could potentially lead to more sensitive and specific diagnostic tests for unilateral vestibular pathologies.…”
mentioning
confidence: 87%
See 4 more Smart Citations
“…3 However, a consistent finding in transient cVEMP IAA literature is a relatively high upper limit of normal for a diagnostic criterion (e.g., upward of 40–45% asymmetry). Clinard et al 4 reported AMcVEMP IAAs for amplitude measures that were similar to IAAs of transient cVEMPs, with upper limits of normal at ∼45%; AMcVEMP interaural asymmetries for SNR and phase coherence had upper limits of ∼15%. This smaller variability in AMcVEMP interaural asymmetries could potentially lead to more sensitive and specific diagnostic tests for unilateral vestibular pathologies.…”
mentioning
confidence: 87%
“…Borrowing from the auditory-evoked potential literature, we recently elicited cVEMPs using bone-conducted, amplitude-modulated (AM) tones, a response termed an amplitude-modulated cervical vestibular-evoked myogenic potential (AMcVEMP). 4 AMcVEMPs have the potential to provide great insight regarding otolith physiology as phase-based analyses can be examined alongside amplitude-based measures yielding new information about human otolith neural synchrony. Further, AMcVEMPs allow for better ways of examining sustained activity and aspects of otolith hair cell nonlinearity.…”
mentioning
confidence: 99%
See 3 more Smart Citations